IPO Underpricing: IPO Stock Performance On The Indonesia Stock Exchange - Novemrian, Yandi; Yunita, Irni (International Journal of Science, Technology & Management, 2025)
This study aims to analyze non-financial factors that influence underpricing in companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange during the period 2021 to 2023. The variables analyzed include industry sector, issue size, underwriter reputation, auditor reputation, and legal consultant reputation. The research employs a quantitative approach with an explanatory design and uses binary logistic regression analysis. The sample consists of 187 firms selected using purposive sampling. The results show that the underpricing phenomenon remains prevalent in Indonesia. Among the variables studied, issue size and auditor reputation have a significant influence on underpricing. These findings indicate the importance of strong market signals in reducing information asymmetry between issuers and investors. This research contributes to the IPO literature in emerging markets and provides practical implications for companies, investors, and capital market authorities.